Exile Literature and Diaspora: The Impact of Exile on Writers and their Work (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Quest for identity, nostalgia for the roots, sense of guilt have consistently been there in the psyche of the writers. The diasporic writers regularly go to their homeland for different reasons like perpetual quest for hisher roots or to deify its history or to re-invigorate ones hurting and aching soul or to remember old memories and so on. Displacement, regardless of whether constrained or purposeful, is from various perspectives a catastrophe. However, an unconventional yet a powerful point to note is that writers in their uprooted presence for the most part will in general exceed expectations in their work, as though the changed air acts as an energizer for them. These writings in disengaged conditions are regularly named as exile writing. Exile has negative connotations however in the event that oneself exile of a Byron is considered, at that point the reaction to that very word gets irresolute. In the event that an all-encompassing perspective on exile is taken, the definition would incorporate transient writers and non-resident writers and in any event, gallivanting writers who meander about for better pastures to brush and fill their oeuvre. World writing has a bounty of writers whose writings have thrived while they were in exile. In spite of the fact that it is preposterous to accept the other way around that exiled writers would not have thrived had they not been in exile, the fact in the previous statement can't be denied. Cultural theorists and literary critics are largely indistinguishable in this view.